Utilization of Moringa Leaf Powder as a Jelly Candy Flavor - Ngakan Putu Sudiarta (Gastronomy Tourism Journal, 2022)
This study aims to determine and describe how the results of the organoleptic test of moringa leaves as jelly candy flavor. Candy in general is a product made by boiling a mixture of sugar and additives that can maintain its shape for a long time with coloring and flavoring agents which are then molded into the desired shape. The data analysis technique used in this study is a qualitative descriptive analysis technique to determine the benefits of moringa leaf powder as a jelly candy flavor, in terms of taste, texture, color and aroma. Based on the organoleptic test conducted by 20 panelists, the taste of the jelly candy received a good interpretation criterion of 79%, and most of the panelists stated that the taste of jelly candy with moringa leaf powder flavor is sweet and has a distinctive taste of moringa. The utilization of moringa leaf powder as jelly candy flavor is good, because it gets a good total interpretation criterion, which is 67%.